The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1479164120909030
|View full text |Cite
|
Sign up to set email alerts
|

Mean and variability of annual haemoglobin A1c are associated with high-risk peripheral artery disease

Abstract: Background: Glucose variability is predictive of cardiovascular events and all-cause mortality. However, the association between peripheral artery disease and glucose variability has not been thoroughly investigated. Therefore, the standard deviation of annual haemoglobin A1c was assessed in patients with type 2 diabetes for evaluating the different risks of peripheral artery disease. Methods: A total of 4144 patients underwent an evaluation for the ankle-brachial index and the percentage of mean arterial pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The baPWV was calculated as (distance from the suprasternal notch to the brachiumdistance from the suprasternal notch to the ankle)/(the time interval between waves detected at the brachium and ankle), where the distances from the suprasternal notch to the brachium and ankle were estimated based on the patient's body height [18]. The reproducibility of the ABI and %MAP has been demonstrated in our previous study [19], and the 95% con dence interval (CI) between repeated measurements of baPWV was 4.95 ± 46.46 cm/sec based on Bland-Altman plots. The lower ABI value and the higher %MAP and baPWV values between lower limbs in an individual were used for the analyses.…”
Section: Assessmentsmentioning
confidence: 91%
See 1 more Smart Citation
“…The baPWV was calculated as (distance from the suprasternal notch to the brachiumdistance from the suprasternal notch to the ankle)/(the time interval between waves detected at the brachium and ankle), where the distances from the suprasternal notch to the brachium and ankle were estimated based on the patient's body height [18]. The reproducibility of the ABI and %MAP has been demonstrated in our previous study [19], and the 95% con dence interval (CI) between repeated measurements of baPWV was 4.95 ± 46.46 cm/sec based on Bland-Altman plots. The lower ABI value and the higher %MAP and baPWV values between lower limbs in an individual were used for the analyses.…”
Section: Assessmentsmentioning
confidence: 91%
“…The lower ABI value and the higher %MAP and baPWV values between lower limbs in an individual were used for the analyses. ABI ≤ 0.90 and %MAP > 45% were de ned as abnormal [13,19].…”
Section: Assessmentsmentioning
confidence: 99%
“…In the present study, the risk factors signi cantly associated with %MAP in both the different ABI groups, included age, CVD history, BMI, HbA1c, eGFR, UACR, baPWV, use of antiplatelet agents, type of oral antihyperglycemic drug, and type of hypertensive drug (Table 1). However, we did not include all cardiovascular risk factors in the present study; for example, a higher HbA1c variability has been previously reported to be associated with a higher %MAP [15]. Furthermore, this study has several limitations.…”
mentioning
confidence: 94%
“…The %MAP value was automatically determined based on the ankle pulse volume waveform during ABI measurement. The reproducibilities of the ABI and %MAP have been demonstrated using Bland-Altman plots in our previous study [15]. The lower ABI value, and the higher %MAP and baPWV values between lower limbs in an individual were used for the analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation